Creating a Vocabulary About School-Age Childcare Using Photography. Issue 1 (19th February 2019) - Bell, Kevin; Cartmel, Jennifer
Engaging children in school-age childcare (SAC) in the research process through the use of photography gives them a voice that is not necessarily heard otherwise. This article discusses a research project undertaken in an Australian SAC service using photography as a means for the children to describe their play experiences. It examines the literature about researching with children using photography and discusses some of the challenges and how these can be overcome in order to provide staff and policy makers in school-age care with understandings about school-age care from the perspectives of the children. SAC plays a significant role in the lives of children and families; however, the research about this service is minimal.